Positive Impacts of the COVID-19 Pandemic and Public Health Measures on Healthcare - Hung Eun Hoo; Hong Chuan Loh; Alan Swee Hock Ch’ng; Fan Kee Hoo; Irene Looi (Progress in Microbes and Molecular Biology)
In the midst of the COVID-19 pandemic, several unexpected positive outcomes have surfaced. The WHO public health measures have positively transformed people’s behaviour and lifestyles. The pandemic has prompted more focus on self-care and health awareness. Hand hygiene practice has been greatly emphasised. The acceptance rate for the use of personal protective equipment, such as face masks, has been remarkable. People with co-morbid conditions are paying more attention to their primary illnesses by improving diets and exercise methods. People are more willing to accept and act on public health messages. The pandemic lockdowns have not only successfully mitigated the transmission of coronavirus, but they have also indirectly reduced the hospital admission rates for endemic community respiratory infections and trauma-related emergencies like motor vehicle accidents. Fetomaternal health and wellness have significantly improved during the pandemic. The abrupt emergence of COVID-19 has also led to a massive societal shift on tobacco smoking cessation. Smokers are compelled to reflect on the harmful effects of cigarette smoking in relation to COVID-19. Issues of mental, relational and sexual health are put in the spotlight during the pandemic. People are investing more time in themselves, family and relationships. The world has seen an unprecedented global race in healthcare innovation and technology development in tackling the same global issue. Artificial intelligence, including robots and drones, have been rapidly developed and employed for healthcare as well as food and delivery services in order to minimise human physical contact. This article discusses several unforeseen positive impacts on healthcare that emerged from the COVID-19 public health measures that have been implemented. The positive impacts of the COVID-19 pandemic should be highlighted in order to provide hope to our community.